Optimal irrigation planning using multi-objective fuzzy linear programming models - Mirajkar, A.B.; Patel, P.L. (ISH journal of hydraulic engineering, 2012)
Crisp linear programming approach has been used to get the individual solutions of three conflicting objectives: maximisation of net benefit, maximisation of employment generation and minimisation of cost of cultivation. These crisp solutions were, then, solved together to obtain the solution under fuzzy multi-objective environment with maximum-minimum operators. Also, an effort has been made to improve the solution from maximum-minimum operator approach using two-phase as well as compromised fuzzy approaches. The applicability of the aforesaid algorithms were demonstrated through a case study of Kakrapar Right Bank Main Canal (KRBMC) under Ukai command area in India.